The Smoot-Hawley Tariff: A Quantitative Assessment - Irwin, Douglas A. (The Review of Economics and Statistics, 1998)
In the two years after the imposition of the Smoot-Hawley tariff in June 1930, the volume of U.S. imports fell over 40%. To what extent can this collapse of trade be attributed to the tariff itself versus other factors such as declining income or foreign retaliation? Partial and general equilibrium assessments indicate that the Smoot-Hawley tariff itself reduced imports by 4-8% (ceteris paribus), although the combination of specific duties and deflation further raised the effective tariff and reduced imports an additional 8-10%. A counterfactual simulation suggests that nearly a quarter of the observed 40% decline in imports can be attributed to the rise in the effective tariff (i.e., Smoot-Hawley plus deflation).